Komunikasi Islam Orang Tua Generasi Z dalam Pembentukan Karakter Anak - Salsabila, Nadia Aura (Journal of Islamic Communication Studies, 2025)
This study aims to understand the communication direction of Generation Z parents in shaping children’s character in Jebung Kidul Village. Using a qualitative descriptive case study, data were collected from ten Generation Z parents aged 20–28 through in-depth interviews and documentation. The results show that their communication patterns are dynamic, alternating between one-way and two-way approaches. One-way communication is used to enforce discipline, while two-way interaction fosters emotional closeness. Parents adopt an affective and supportive communication style emphasizing empathy, positive reinforcement, and reflective dialogue. Traditional and religious values are transmitted through modeling and daily habituation, allowing children’s character to form naturally. Generation Z parents act as cultural mediators who integrate traditional and modern values through reflective communication that strengthens moral reasoning, emotional intelligence, and independence in the digital era.